Thanius biennis, a new gall-inducing weevil with a two-year life-cycle from Costa Rica (Coleoptera: Curculionidae: Baridinae). - Prena, Jens; Nishida, Kenji (Contributions to Entomology = Beiträge zur Entomologie, 2005)
Thanius biennis Prena & Nishida sp. n. is described and illustrated. The larva induced galls on stems of Psychotria marginata (Rubiaceae). The complete life-cycle took two years per generation, and two alternate generations coexisted on the same plant. Each gall harbored a single immature or adult specimen. The latter stage remained dormant in the gall for nearly five months, and emerged with the beginning of the rainy season. Resumen Thanius biennis Prena & Nishida sp. n. es descrito e ilustrado. Las larvas se encontraron induciendo agallas en ramas de Psychotria marginata (Rubiaceae). Se duraron dos años para completar su ciclo de vida y dos generaciones coexisten en la misma planta. Cada agalla contiene un sólo individuo de estadio inmaduro o adulto. El adulto se quedó inactivo en la agalla por cerca de cinco meses y emergió en el principio de la época lluviosa. Keywords weevils, Thanius, Rubiaceae, Psychotria, galls, Calliephialtes, Neotropics. Nomenclatural Acts biennis Prena & Nishida, 2005 (Thanius), spec. n.